Scale of Sexual Prejudice Against Bisexuals: Evidence of Validity - Nicácio De Freitas Nery, Nathália (2023)
Sexual prejudice against bisexuals is widespread in society. However, little research has been done on this phenomenon because it is difficult to measure. The aim of the current study was to validate a short version of the Biphobia Scale for the Brazilian context (EPSB-br). In the first study, the EPSB-br showed unifactorial structure and convergent validity with scales measuring beliefs and stereotypes about bisexuality. Study 2 showed the EPSB-br’s convergent-discriminant validity with scales measuring religiosity, right-wing authoritarianism, social dominance orientation, and sleepiness. Finally, Study 3 demonstrated the criterion-related validity of the EPSB-br through an experimental manipulation in which participants watched a video of a pretend teacher and assigned a salary to it. Taken together, these results showed evidence of validity and reliability of the EPSB-br, which introduced a measure of prejudice against bisexual people in Brazil.